2022
DOI: 10.3390/met12030530
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microstructural and Mechanical Behavior of AHSS CP780 Steel Welded by GMAW-Pulsed and GMAW-Pulsed-Brazing Processes

Abstract: Joints of complex phase 780 (CP-780) advanced high strength steel (AHSS) were carried out by using an ER-CuAl-A2 filler metal for the gas metal arc welding pulsed brazing (GMAW-P- brazing) process and the ER-80S-D2 for the GMAW-P process employing two levels of heat input. The phases in the weld bead and HAZ were analyzed, and the evaporation of zinc by means of scanning electron microscopy (SEM) was also monitored. The mechanical properties of the welded joints were evaluated by tension, microhardness and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this test, the residual depth is an appropriate criterion for evaluating the wear resistance of the material. This test is frequently used to compare the wear resistance of various materials processed in different conditions [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. The AFM images from longitudinal scratches of the bulk As can be seen, the residual depth of the Fe 3 Al compound is larger than that of the (Fe,Ti) 3 Al sample.…”
Section: Resultsmentioning
confidence: 99%
“…In this test, the residual depth is an appropriate criterion for evaluating the wear resistance of the material. This test is frequently used to compare the wear resistance of various materials processed in different conditions [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. The AFM images from longitudinal scratches of the bulk As can be seen, the residual depth of the Fe 3 Al compound is larger than that of the (Fe,Ti) 3 Al sample.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the interface WM-XP1000, the hardness is 238-270 HV100 and can be associated with the high concentration of Widmanstätten ferrite, which grows from ferritic grains with the precipitation of lamellar cementite. The microhardness is influenced by the microstructure and is dependent on welding parameters such as current and voltage, which play an important role in the heat input supplied [29,30]. Based on the results, it can be observed that the use of a suitable experimental arrangement allows better conditions to be obtained, such as the decrease in porosities as well as their diameter, e.g., in the case of trial 1.…”
Section: Microhardness Profiles Meassurementmentioning
confidence: 96%
“…In the case of the interface WM-XP1000, the hardness is 238-270 HV 100 and can be associated with the high concentration of Widmanstätten ferrite, which grows from ferritic grains with the precipitation of lamellar cementite. The microhardness is influenced by the microstructure and is dependent on welding parameters such as current and voltage, which play an important role in the heat input supplied [29,30].…”
Section: Microhardness Profiles Meassurementmentioning
confidence: 99%